Neural process of emotional arousal from the Malaysian affective picture system: a P300 study - Ramli, Nur Adila (2018)
The terminology of the emotions has been described simply as adaptive action disposition where it applied to the organism for either approach or avoidance related behaviors. This study title as ‘Neural process of emotional arousal from the Malaysian Affective Picture system: A P300’. Through this study, deeper observation was conducted in order to identify the differences of the latency and amplitude of P300 ERP component across the level of arousal in Malaysian Affective Picture and to visualize and analyze the source of P300 ERP component across the level of arousal in Malaysian Affective Picture using 128-electrode sensor net. There are two phases that were implemented in this study, which the first phase is known as Affective measure of the Malaysian Picture with 47 participants and the Event Related Potential for second phase with 32 participants. Students with neuropsychological disorders and alcohol dependents are excluded. Participants completed the passive paradigm by focusing and responding to the stimuli that have been presented to them. The amplitude, latency and the source of P300 ERP component were observed and determined. The results obtained were analyzed using ‘One way-repeated measure ANOVA’ from seven electrode sites (Fz, Cz, Pz, C3, C4, P3 and P4). The analysis revealed that there is no significant difference for the latency and there are significant differences in amplitude across levels of arousal showed by the electrodes of C3 and P4 sites, the localization also showed that there were no emotional features involved in this study. Thus, the future research needs to include varying types of emotional stimuli (high arousal stimuli with unpleasant valence value).